2019
DOI: 10.1101/673251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput multiplexed tandem repeat genotyping using targeted long-read sequencing

Abstract: 3Tandem repeats (TRs) are highly prone to variation in copy numbers due to their repetitive and 2 4 unstable nature, which makes them a major source of genomic variation between individuals. 5However, population variation of TRs have not been widely explored due to the limitations of 2 6 existing tools, which are either low-throughput or restricted to a small subset of TRs. Here, we 2 7used SureSelect targeted sequencing approach combined with Nanopore sequencing to 2 8 overcome these limitations. We achieved … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For the second challenge, a previous study [10] performed a comprehensive survey and then demonstrated that Stampy [12] was the most accurate with regards to mapping reads in STR regions, while Novoalign (http:// www.novocraft.com), Bowtie2 [13] and BWA [14] consumed much shorter running times. For the third challenge, research demonstrated that long-read sequencing technologies (such as Nanopore or PacBio) could potentially sequence through larger repeat loci with accuracy and effective cost [15]. Furthermore, short paired-end reads with sequence overlaps can be assembled to create longer sequences, and assembled reads will span the full length of the original DNA fragment.…”
Section: Introductionmentioning
confidence: 99%
“…For the second challenge, a previous study [10] performed a comprehensive survey and then demonstrated that Stampy [12] was the most accurate with regards to mapping reads in STR regions, while Novoalign (http:// www.novocraft.com), Bowtie2 [13] and BWA [14] consumed much shorter running times. For the third challenge, research demonstrated that long-read sequencing technologies (such as Nanopore or PacBio) could potentially sequence through larger repeat loci with accuracy and effective cost [15]. Furthermore, short paired-end reads with sequence overlaps can be assembled to create longer sequences, and assembled reads will span the full length of the original DNA fragment.…”
Section: Introductionmentioning
confidence: 99%